2017
DOI: 10.1002/elsc.201500148
|View full text |Cite
|
Sign up to set email alerts
|

Determination of bubble size distribution in gas–liquid two‐phase systems via an ultrasound‐based method

Abstract: Over the past few years, ultrasonic techniques are increasingly used to determine bubble size distribution in gas-liquid two-phase systems. However, the development of a precise and efficient measuring system is very challenging because bubbles are dynamic and unstable relative to time and space in a moving fluid, thus hindering an accurate validation of the measuring system. Therefore, this study examined the possibility of using artificial bubbles to establish an ultrasonic measuring system. The main concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
(47 reference statements)
0
5
0
1
Order By: Relevance
“…In contrast, the bubble size distribution technique evaluates increases in bubble size over time as a measure of stability. Several methods have been developed to ascertain bubble size distribution, including visual, electro-resistivity and acoustic techniques [36].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the bubble size distribution technique evaluates increases in bubble size over time as a measure of stability. Several methods have been developed to ascertain bubble size distribution, including visual, electro-resistivity and acoustic techniques [36].…”
Section: Introductionmentioning
confidence: 99%
“…The ultrasonic method offers the great advantage that the bioreactor does not have to be transparent. It has been shown that comparable results can be achieved with ultrasonic and optical methods [121]. Shadowgraphy measurements belong to the optical measurement methods.…”
Section: Bubble Size Distribution Measurementmentioning
confidence: 92%
“…Essential extrusive methods include laser doppler anemometry (LDA) [117][118][119], ultrasonic [120][121][122][123][124] and shadow imaging (shadowgraphy) [125][126][127][128]. For LDA measurement, two laser beams cross each other in the transparent bioreactor.…”
Section: Bubble Size Distribution Measurementmentioning
confidence: 99%
“…Rodrigues and Rubio [9] classified them into intrusive and nonintrusive methods. The intrusive methods include electroresistivity [43][44][45][46], ultrasound reflection [47][48][49][50][51], and optical techniques [52][53][54][55][56][57][58], which inevitably cause instrumented interference on bubble samples. In comparison to those approaches, the imaging technique as a nonintrusive method has been primarily adopted for both academic and industry bubble size measurement due to lower cost and ease of operation [5,9,15,16,28,30,59].…”
Section: Introductionmentioning
confidence: 99%